2022
DOI: 10.3390/ma15134500
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Pore Structure Characteristics and Crack Propagation Behavior of Coal Samples from High Gas Seam

Abstract: Investigation on the pore-fracture features and crack propagation behavior of coal is necessary to prevent coal mine disasters. The pore structure features of coal samples taken from high gas seam were obtained by mercury injection porosimetry (MIP) and gas adsorption methods. The process of deformation and failure for coal samples under three-point bending conditions were obtained. The results demonstrate that the adsorption pores with diameter less than 100 nm are the most developed and their surfaces are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Fractal dimension is a method used to express the irregularity and complexity of porous media [41][42][43][44]. The fractal dimension is between 2 and 3.…”
Section: Raw Coalmentioning
confidence: 99%
“…Fractal dimension is a method used to express the irregularity and complexity of porous media [41][42][43][44]. The fractal dimension is between 2 and 3.…”
Section: Raw Coalmentioning
confidence: 99%
“…However, due to the fact that the type of coal cannot reproduce the real fracture structure of raw coal, the experimental results are different from the actual situation. At present, scanning electron microscopy, CT scanning, MIP, nitrogen adsorption, and NMR technology are increasingly used in the characterization of the fracture structure of coal rock. Many scholars have made important achievements in the study of coal imbibition based on the above testing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that in virgin gas-bearing coal seams, fractures are influenced by both rock pressure and gas pressure within the coal seam fissures. Zhu et al (2022) used mercury intrusion porosimetry and gas adsorption methods to investigate the pore structure characteristics of coal samples from highly gassy coal seams. The results indicated that during the initial stage of crack propagation, the main cracks on the coal samples extended along the direction of natural fractures.…”
Section: Introductionmentioning
confidence: 99%